Adipokines and Inflammation Alter the Interaction Between Rheumatoid Arthritis Synovial Fibroblasts and Endothelial Cells - Hasseli, Rebecca; Frommer, Klaus W.; Schwarz, Maria; Hülser, Marie-Lisa; Schreiyäck, Carina; Arnold, Mona; Diller, Magnus; Tarner, Ingo H.; Lange, Uwe; Pons-Kühnemann, Joern; Schönburg, Markus; Rehart, Stefan; et al. (Frontiers in Immunology, 2020)
Objective: The long-distance migration of rheumatoid arthritis synovial fibroblasts (RASF) in the severe combined immunodeficiency (SCID) mouse model of rheumatoid arthritis (RA) suggests that an interaction between RASF and endothelial cells (EC) is critical in this process. Our objective was to assess whether immunomodulatory factors such as adipokines and antirheumatic drugs affect the adhesion of RASF to EC or the expression of surface molecules. Methods: Primary EC or human umbilical vein endothelial cell (HUVEC) and primary RASF were stimulated with adiponectin (10 µg/ml), visfatin (100 ng/ml) and resistin (20 ng/ml) or treated with methotrexate (1.5 µM and 1000 µM) and the glucocorticoids prednisolone (1 µM) and dexamethasone (1 µM), respectively. The expression of adhesion molecules was analysed by real-time PCR. The interaction of both cell types was analysed under static (cell-to-cell-binding assay) and dynamic conditions (flow adhesion assay). Results: Under static conditions, adipokines increased mostly binding of RASF to EC (adiponectin: 40%, visfatin: 28%, TNF-α: 49%). Under flow conditions, visfatin increased RASF adhesion to HUVEC (e.g. 0.5 dyn/cm2: 75.2%). Reduced adhesion of RASF to E-selectin was observed after treatment with dexamethasone (e.g. 0.9 dyn/cm2: -40%). In EC, TNF-α increased expression of Intercellular Adhesion Molecule-1 (ICAM-1) (20-fold) and Vascular cell adhesion protein-1 (VCAM-1) (77-fold), while P-selectin was downregulated after stimulation with TNF-α (-6-fold). Conclusion: The adhesion of RASF to EC was increased by visfatin under static and flow conditions, while glucocorticoids were able to decrease adhesion to E-selectin. The process of migration and adhesion of RASF to EC could be enhanced by adipokines via adhesion molecules and seems to be targeted by therapeutic intervention with glucocorticoids.